1997
DOI: 10.1002/crat.2170320118
|View full text |Cite
|
Sign up to set email alerts
|

Certification of Reference Material with Special Emphasis on Porous Solids

Abstract: Certified reference materials (CRMs) are very important for the reliability of the results of chemical analyses and, at the same time, constitute the basis of comparability of analytical data. The development of a new type of CRMs is demonstrated using the example of porous and finely dispersed solids having specific surface area, specific pore volume, pore volume distribution, and mean pore radius as their characteristic values.Many of the properties of reference materials to be certified, such as their eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Goldstein [25], which describes exactly how to apply the X-ray diffraction method to determine porosity. Also, in the work of K. Meyer et al [26], a detailed diagram of the applicability of various analysis methods is provided for determining the porosity, according to which X-ray and neutron diffraction methods are applicable in the pore size range from fractions of nanometers to 100-300 nm, which agrees closely with the pore sizes observed in the studied ceramic samples. The use of X-ray diffraction techniques for the characterization of porous materials is also presented in [27,28].…”
Section: Methodssupporting
confidence: 54%
“…Goldstein [25], which describes exactly how to apply the X-ray diffraction method to determine porosity. Also, in the work of K. Meyer et al [26], a detailed diagram of the applicability of various analysis methods is provided for determining the porosity, according to which X-ray and neutron diffraction methods are applicable in the pore size range from fractions of nanometers to 100-300 nm, which agrees closely with the pore sizes observed in the studied ceramic samples. The use of X-ray diffraction techniques for the characterization of porous materials is also presented in [27,28].…”
Section: Methodssupporting
confidence: 54%
“…Li et al demonstrated in a study of shale samples from the southeast Chongqing area (China) that the Stoeckli et al method for CO 2 adsorption analysis can provide simple pore size distribution characterization of micropores. The pore range in which adsorption analysis is generally considered to be viable is 0.25 nm < porosity < ∼800 nm (2.5 Å < porosity < 8000 Å). , …”
Section: Materials and Methodsmentioning
confidence: 99%
“…The pore range in which adsorption analysis is generally considered to be viable is 0.25 nm < porosity < ∼800 nm (2.5 Å < porosity < 8000 Å). 45,46 2.4. Rock-Eval Pyrolysis.…”
Section: Samples Their Preparation and General Characteristicsmentioning
confidence: 99%